Catalyzing the scale-up of crop biofortification - Baral, Arun; Birol, Ekin (International Food Policy Research Institute, 2020)
Globally, an estimated two billion people suffer from micronutrient deficiencies that contribute to weakened immune systems, disease, disability, and even death.1 One of the main causes of micronutrient deficiencies – also known as hidden hunger – is low-quality diets that rely on calorie-rich but micronutrient-poor staple crops, and include very little nutrientdense foods such as animal-sourced foods and fresh fruits and vegetables.